2017
DOI: 10.1617/s11527-016-0990-6
|View full text |Cite
|
Sign up to set email alerts
|

Bond between microwave cured repair and concrete substrate

Abstract: The bond strength between a concrete substrate and repair patch is critical to its durability. This paper investigates the effect of microwave curing the freshly applied repair, for 45 min at 132 Watts, on the 28 day bond strength between substrate concrete and different commercial repair materials. The repairs were applied at different ambient temperatures of 20, 10, 2 and -5°C. Tensile split tests on repaired cube specimens were performed to determine the interfacial bond strength. The ability of microwave c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This impact is likely to be more significant when microwave curing is used under normal ambient temperatures than under cold weather conditions. Recent research has shown much greater benefit of microwave curing in cold weather conditions [21].…”
Section: Microwave Cured Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact is likely to be more significant when microwave curing is used under normal ambient temperatures than under cold weather conditions. Recent research has shown much greater benefit of microwave curing in cold weather conditions [21].…”
Section: Microwave Cured Specimensmentioning
confidence: 99%
“…This research investigation reports the relationship between test results of internal and surface temperatures monitored on specimens of concrete repair mortars. The authors have previously reported on the parameters of microwave curing which affect the strength and other properties of concrete repair materials [20] including bond between a repair patch and both the substrate concrete and the steel reinforcement [21,22]. However, the interaction between microwave curing and hydration temperatures at early age can have significant effect on the properties and long term deterioration processes in concrete repair patches [23].…”
Section: Introductionmentioning
confidence: 99%
“…It deals with the bond of plain steel reinforcement embedded in different concrete repair materials. Another aspect of bond strength which is of critical importance for the efficient performance of concrete repair is the interfacial bond between the substrate concrete and patch repair, which has been reported elsewhere [16].…”
Section: Introductionmentioning
confidence: 87%
“…The reduction is due to loss of free water in the form of vapour and it depends on the mix proportions, cement replacement materials and admixtures used in the proprietary repair formulations. Shrinkage is a detrimental property of repair materials and a major cause of patch repair failure in service life often due to bond failure at the repair interface [16]. Manufactures often use shrinkage reducing admixtures or expansive cement as shrinkage compensators in repair materials.…”
Section: Effect Of Microwave Curing On Shrinkagementioning
confidence: 99%